Pitch corrections occur in natural speech and are abnormal in patients with Alzheimer's disease - Subrahmanya, Anantajit; Ranasinghe, Kamalini G.; Kothare, Hardik; Raharjo, Inez; Kim, Kwang S.; Houde, John F.; Nagarajan, Srikantan S. (Frontiers in Human Neuroscience, 2024)
Past studies have explored formant centering, a corrective behavior of convergence over the duration of an utterance towards the formants of a putative target vowel. In this study, we establish the existence of a similar centering phenomenon for pitch in healthy elderly controls and examine how such corrective behavior is altered in Alzheimer's Disease (AD). We found the pitch centering response in healthy elderly was similar when correcting pitch errors below and above the target (median) pitch. In contrast, patients with AD showed an asymmetry with a larger correction for the pitch errors below the target phonation than above the target phonation. These findings indicate that pitch centering is a robust compensation behavior in human speech. Our findings also explore the potential impacts on pitch centering from neurodegenerative processes impacting speech in AD.